The Association of Epstein-Barr Virus Antibodies with Cancer Patients among Yemeni Patients - Abdullah, Qais Y M; Alghalibi, Saeed M S; Al-Mahbashi, Anas A; Al-Khalqi, Eshraq A (PSM Microbiology, 2021)
The Epstein–Barr virus (EBV) is the causative agent of infectious mononucleosis and has been linked to several malignancies. Seroepidemiological studies have shown that approximately 90%–95% of individuals worldwide are infected with EBV. This study aimed to determine the seroprevalence of EBV among cancer patients compared with healthy controls in Sana’a city, Yemen, and determine the clinical characteristics and some risk factors associated with EBV infection. One hundred subjects were enrolled in the study. Fifty individuals were clinically diagnosed to have cancer. The remaining 50 individuals were healthy controls. Serum IgG and IgM antibodies against EBV viral capsid antigen (VCA) were tested by an enzyme-linked immunosorbent assay (ELISA). The results showed that the prevalence rate of EBV-VCA IgG and IgM antibodies among cancer patients was 94% and 12% while in healthy individuals was 82% and 8%, respectively. Most common symptoms were pharyngitis, fever, and fatigue. Moreover, educational level, income status, residency, consuming Shammah, and blood transfusion were found as significant risk factors for EBV infection. Therefore, this study concluded that Sana’a city is one of the endemic areas in Yemen, and the incidence of cancer types in the present study is associated with EBV infection.